Evaluasi Kinerja Embung Kecil di Kabupaten Kupang - Since Deta Adelfina Fallo; I Made Udiana; Sudiyo Utomo (Universitas Nusa Cendana, 2022)
The construction of a small dam in the Kupang District aims to help supply water needs for the agricultural sector, livestock sector, and human needs during the dry season. This study aimed to evaluate the performance of 30 small dams built in Kupang Regency through three aspects, namely physical aspects, utilization aspects, and operation and maintenance aspects. The method used is the Survey Method, Descriptive Analysis and the Likert Scale Method. The results showed that the performance of the small dam's physical aspects in Kupang Regency was in bad condition, with a bad percentage value of 73.23%. The minor dam utilization aspects in Kupang Regency were in good condition with a good percentage value of 55.75%. The operation and maintenance aspects of the small dam in Kupang Regency were in bad condition, with a bad percentage value of 63.74%. Overall, the percentage of small dams studied in the Kupang Regency that experienced a decline in function was 69.63%, and the percentage of small reservoirs that were still functioning was 31.37%.